Manufacturing method of automobile structural part

By using amorphous thermoplastic resin as a solid bonding agent, efficiently bonding the different metal components in the automotive structural parts, solving the problems of insufficient lightweighting and electrocorrosion, and achieving high bonding strength and fuel economy.

CN119522174APending Publication Date: 2025-02-25RESONAC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380052393.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-08
Filing Date
2023-06-30
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing automotive structural parts and reinforcements have insufficient lightweighting in ensuring collision safety and fuel economy, and traditional bonding methods are difficult to achieve high bonding strength and prevent electrical corrosion.

Method used

Amorphous thermoplastic resin is used as a solid bonding agent, and it is melted by heating and pressurization, and different metal components such as aluminum alloy and steel are bonded to achieve high bonding strength and suppress electrocorrosion.

Benefits of technology

It realizes efficient and lightweighting and high bonding strength of automotive structural parts, avoids electrocorrosion problems, and improves productivity and freedom of manufacturing processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522174A_ABST
    Figure CN119522174A_ABST
Patent Text Reader

Abstract

A method for manufacturing an automobile structural member according to an embodiment includes: a pre-bonding step for preparing a laminate in a state in which a first metal member, a solid-state adhesive having an amorphous thermoplastic resin as a main component, and a second metal member are arranged in this order, and a bonding step for bonding the first metal member, the solid-state adhesive, and the second metal member; the amorphous thermoplastic resin is at least one of a thermoplastic epoxy resin and a phenoxy resin, and in the bonding step, the laminate is heated and pressurized to melt the solid binder and bond the first metal member and the second metal member, and the Young's modulus of the second metal member is higher than the Young's modulus of the first metal member by 5 GPa or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for manufacturing an automobile structural part. Background Art

[0002] Automobile structural parts and reinforcements, such as panels (outer and inner panels such as hood, door, roof, etc.), bumper reinforcements (bumper R / F), door anti-collision beams, etc., are required to be lightweight in order to improve fuel economy while ensuring safety against collisions.

[0003] For example, a bumper structure including a bumper reinforcement is installed at the front and rear of a car to absorb energy from an external collision and protect the vehicle body and the passenger space. Fig. 9 As shown, the bumper panel 10 , the energy absorber 20 , the bumper reinforcement 30 , the crash box 40 , and the vehicle body fixing member 50 are provided in this order from the outside.

[0004] Patent document 1 (Japanese Patent Publication No. 2011-20471) states: "A structural member for a vehicle, characterized in that it is a structural member for a vehicle with a closed cross-sectional shape and having a long cap member, the cap member having two wall portions arranged opposite to each other, two bottom corner portions formed continuously with one end point of each of the two wall portions, and a cross-sectional shape of a bottom that connects the two bottom corner portions, and is used to absorb collision energy by bending deformation caused by an impact load in a direction substantially parallel to the cross-sectional shape, the cap member is composed of a first member constituting at least a part of the bottom and a plurality of second members constituting the wall portion and having a plate thickness greater than the plate thickness of the first member, both ends of the first member in the width direction overlap with one end of each of the second members in the width direction, and, in the overlapping portion of the first member and the second member, a welding portion for joining the first member and the second member is formed by extending in the length direction of the cap member"; it is also recorded that: the structural member for a vehicle is a bumper reinforcement.

[0005] Patent document 2 (Japanese Patent Publication No. 2007-284039) states: "A bumper structure, characterized in that it is composed of a bumper reinforcement and a cylindrical bumper bracket, the bumper reinforcement is composed of a metal profile with a hollow cross-section, the bumper bracket is made of an aluminum alloy and is fixed to both ends of the bumper reinforcement, the bumper reinforcement has a profile composed of a front wall and a rear wall and upper and lower walls connecting them, and holes penetrating the front wall and the rear wall are formed at both ends, the axial direction of the bumper bracket is oriented in the front-rear direction of the vehicle body, a shaft portion is embedded in the hole of the bumper reinforcement, the shaft portion is expanded by electromagnetic forming so as to be in close contact with the inner peripheral surface of the hole, and protrudes in the outer diameter direction between the front wall and the rear wall, the cross-sectional structure of the upper and lower walls is designed to bend toward the hollow inner side when buckled by a compressive load in the front-rear direction, the outer peripheral surface of the protruding shaft portion of the bumper bracket is opposite to the inner surface of the upper and lower walls, and touches the shaft portion when the upper and lower walls are buckled."

[0006] Patent document 3 (Japanese Patent Gazette No. 2011-161466) states: "When the steel plates 10, 11 stacked on the back side of the rear surface side flange 4 of the aluminum alloy hollow profile 2 having a sun-shaped cross-section with a center rib provided in a rectangular cross-section are welded together at three locations: the two end sides 4b, 4c of the rear side flange 4 and the central side 4a where the center rib 7 of the rear side flange 4 intersects, the back area of ​​the above-mentioned central side 4a is pre-formed into a convex shape 8, the convex part 8 is sandwiched in the middle, and the two above-mentioned steel plates are stacked in a manner that the convex part 8 protrudes between the steel plates, and arc welding is performed by FCW in this state."

[0007] Patent document 4 (Japanese Patent Publication No. 2018-161946) states: "A vehicle structure, comprising: a tubular first member having a protrusion on the outer periphery, and a tubular second member having a retaining wall formed with a hole portion capable of inserting the first member, an insertion portion of the first member inserted into the hole portion of the second member is expanded and joined to the second member, and the protrusion abuts against the retaining wall of the second member."

[0008] Prior Art Literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2011-20471

[0011] Patent Document 2: Japanese Patent Application Publication No. 2007-284039

[0012] Patent Document 3: Japanese Patent Application Publication No. 2011-161466

[0013] Patent Document 4: Japanese Patent Application Publication No. 2018-161946 Summary of the invention

[0014] From the perspectives of collision safety, improvement of fuel economy, and enhancement of driving stability, there is a strong demand for automotive structural parts and reinforcement parts to be lightweight while maintaining mechanical properties such as strength, rigidity, and impact absorption.

[0015] For example, the following performance is required for the bumper reinforcements installed at the front and rear of the car: with respect to the load during a collision, they should exhibit high rigidity for light loads and produce plastic deformation for heavy loads to absorb a high degree of energy. Fig.10 As shown in FIG. 1 , when the bumper reinforcement 30 is subjected to a heavy load W, if it is bent without plastic deformation or is excessively plastically deformed, the crash box 40 disposed on the vehicle body side is not crushed, and therefore the impact energy cannot be absorbed by the crash box 40. As a result, the bumper structure cannot efficiently absorb the energy during the external collision, and therefore there is a possibility that the vehicle body and the passenger space cannot be fully protected.

[0016] like Fig. 9 As shown, the bumper reinforcement 30 is arranged along the vehicle width direction ( Fig. 9 The metal bumper reinforcement is a long and narrow member extending in the ±y direction of the vehicle body and is generally formed of a metal material such as aluminum or iron. The metal bumper reinforcement is designed to be lightweight by having a hollow structure. However, the lightweighting is not sufficient in the bumper reinforcement having a hollow structure with a cross-sectional shape for exerting the above-mentioned performance.

[0017] Research is underway to simultaneously achieve improvements in mechanical properties such as strength and rigidity and weight reduction by incorporating different metal materials into a portion of the structure of metal automotive structural parts and reinforcements. As an example of multi-materialization, a combination of steel and aluminum alloy is known, as described in Patent Documents 3 and 4.

[0018] In multi-materialization, components containing dissimilar metals or alloys are fastened together using mechanical joining means such as bolts and nuts, screw clamps, rivets, etc., welded by arc welding, etc., or joined by bonding using adhesives such as liquid or B-stage thermosetting epoxy resin adhesives, hot melt adhesives containing thermoplastic resins, etc.

[0019] Fastening using mechanical joining means is localized, so it is difficult to obtain uniform bonding strength throughout the entire structure or reinforcement. Regarding welding, brittle intermetallic compounds are sometimes generated at the joint, making it difficult to obtain high bonding strength. During fastening and welding, if two metals with different ionization tendencies come into contact, galvanic corrosion (also known as galvanic corrosion) may occur, causing one metal to corrode.

[0020] Regardless of whether the thermosetting epoxy resin adhesive is in the liquid type or the B-stage state, the bonding process time is long or the open time is short. Hot melt adhesives with a short bonding process time and a long open time cannot stably obtain high bonding strength. In addition, these adhesives, especially thermosetting epoxy resin adhesives, show high fluidity in the bonding process, so it is difficult to bond components containing dissimilar metals or alloys in a state of being reliably separated, which is insufficient for preventing galvanic corrosion.

[0021] In the present disclosure, the so-called bonding process time means: the time from the starting point to the end point, starting from the time when the bonding agent first contacts one or both substrates constituting the bonded body, and ending at the time when the production of the bonded body is completed. For example, the bonding process time includes the time required for the coating process and drying process of the liquid adhesive or the loading process of the solid bonding agent, and the time required for bonding the substrates to each other (for example, curing the bonding layer). The shorter the bonding process time, the more the productivity of the bonded body can be improved.

[0022] In the present disclosure, the so-called open time means: the time limit from coating or placing the bonding agent on one substrate (e.g., the first metal component) to the completion of placing the other substrate (e.g., the second metal component). If the open time is within the open time, the bonding force of the bonding agent does not decrease and the substrates can be bonded together with sufficient bonding force. The longer the open time, the greater the degree of freedom of the manufacturing process of the bonded body.

[0023] The present disclosure provides a method for manufacturing an automobile structural part that can join dissimilar metal members with high joining strength, can suppress galvanic corrosion between the dissimilar metal members, has a short joining process time and a long open time.

[0024] The present disclosure includes the following aspects.

[0025] [1] A method for manufacturing an automobile structural part, comprising a pre-joining step and a joining step.

[0026] In the pre-joining step, a laminated body is prepared in which a first metal member, a solid bonding agent, and a second metal member to be joined to the first metal member are sequentially arranged, the solid bonding agent contains an amorphous thermoplastic resin as a main component, and the amorphous thermoplastic resin is at least one of a thermoplastic epoxy resin and a phenoxy resin.

[0027] In the bonding step, the stacked body is heated and pressurized to melt the solid bonding agent to bond the first metal member and the second metal member.

[0028] The Young's modulus of the second metal member is higher than the Young's modulus of the first metal member by 5 GPa or more.

[0029] [2] The method for manufacturing an automobile structural part according to [1],

[0030] The epoxy equivalent of the amorphous thermoplastic resin is 1600 or more, or the amorphous thermoplastic resin does not contain an epoxy group, and the heat of fusion of the amorphous thermoplastic resin is 15 J / g or less.

[0031] [3] The method for manufacturing an automobile structural part according to [1] or [2],

[0032] The heating and pressurizing are performed under the conditions of 100 to 400° C. and 0.01 to 20 MPa.

[0033] [4] The method for manufacturing an automobile structural part according to any one of [1] to [3],

[0034] The solid bonding agent before melting has any shape selected from the group consisting of a film, a rod, a pellet, and a powder.

[0035] [5] The method for manufacturing an automobile structural part according to any one of [1] to [4],

[0036] The automobile structural part is a bumper reinforcement.

[0037] The first metal member is a main body extending in the vehicle width direction and having at least one first joint portion.

[0038] The second metal member is a metal reinforcement portion extending in the vehicle width direction and having at least one second joint portion.

[0039] The first joining portion of the main body portion and the second joining portion of the metal reinforcement portion are joined by the solid bonding agent.

[0040] [6] The method for manufacturing an automobile structural part according to [5],

[0041] The metal reinforcement portion is arranged closer to the vehicle body side than the main body portion.

[0042] [7] The method for manufacturing an automobile structural part according to [5] or [6],

[0043] The main body has an open cross section, and the first joining portion of the main body and the second joining portion of the metal reinforcement are joined to form a cavity inside the main body.

[0044] [8] The method for manufacturing an automobile structural part according to any one of [5] to [7],

[0045] The cross-section of the main body is in a hat shape.

[0046] [9] The method for manufacturing an automobile structural part according to any one of [5] to [8],

[0047] The metal reinforcement portion has one or more holes.

[0048]

[10] The method for manufacturing an automobile structural part according to any one of [5] to [9],

[0049] The material of the main body is an aluminum alloy having a tensile strength of 350 MPa or more.

[0050]

[11] The method for manufacturing an automobile structural part according to any one of [5] to

[10] ,

[0051] The material of the metal reinforcement part is any one metal material selected from iron, steel, Al-Si series aluminum alloy and Al-Zn series aluminum alloy.

[0052]

[12] The method for manufacturing an automobile structural part according to any one of [5] to

[11] ,

[0053] The main body has the first joining portion at the upper and lower parts thereof, respectively.

[0054] The metal reinforcement part has:

[0055] a reinforcement portion main body extending in the vehicle width direction; and

[0056] The second joining parts are respectively provided on the upper and lower parts of the reinforcing part body,

[0057] The first joining portion and the second joining portion are joined at a joining surface intersecting with the front-rear direction of the vehicle.

[0058] According to the manufacturing method of the present disclosure, an automobile structural part can be manufactured with a short joining process time and a long open time, dissimilar metal members of the automobile structural part can be joined with high joining strength, and galvanic corrosion therebetween can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 This is a schematic perspective view of a bumper reinforcement according to an embodiment.

[0060] Figure 2 This is a schematic perspective view of a main body portion of one embodiment.

[0061] Figure 3 This is a schematic perspective view of a metal reinforcement portion according to an embodiment.

[0062] Figure 4 yes Figure 1 AA line cross-section diagram.

[0063] Figure 5 It is a cross-sectional view showing the dimensions of the main body 200 and the metal reinforcement 300 according to one embodiment.

[0064] Figure 6 It is a cross-sectional view of a bumper reinforcement according to another embodiment.

[0065] Figure 7 It is a cross-sectional view showing the dimensions of the main body 500 and the metal reinforcement 600 according to another embodiment.

[0066] Figure 8 It is a schematic diagram of the evaluation device in the three-point bending test.

[0067] Fig. 9 It is a schematic perspective view showing the bumper structure of a vehicle.

[0068] Fig.10 This is a schematic diagram showing the situation in which an impact load is applied to the easily broken bumper reinforcement member disposed on the crash box.

[0069] Fig.11 This is a schematic diagram of a case where an impact load is applied to a bumper reinforcement of one embodiment disposed on a crash box.

[0070] Fig.12 It is a schematic cross-sectional view showing a state in which a first metal member and a second metal member are bonded together via an adhesive layer containing a solid bonding agent. DETAILED DESCRIPTION

[0071] The embodiments of the present disclosure are described in detail below with reference to the drawings. The present disclosure is not limited to the following embodiments, and can be implemented with various modifications within the scope of the gist of the invention.

[0072] In the present disclosure, when a numerical value is expressed in a range, the numerical values ​​at both ends are an upper limit and a lower limit, respectively, and are included in the range.

[0073] In this disclosure, the terms "the front direction of the vehicle" and "the rear direction of the vehicle" mean Fig. 9 The x direction and -x direction of the vehicle, the so-called "upward direction of the vehicle" and "downward direction of the vehicle" mean Fig. 9 The z direction and -z direction of the vehicle, the so-called "width direction of the vehicle" means Fig. 9 ±y direction. In the present disclosure, the so-called "vehicle" means the entire automobile, and the so-called "body" means the part located closer to the inside of the vehicle than the bumper structure and carrying passengers or cargo. In the following description, when there is no special description and when, for example, the up-down direction, the front-back direction, and the width direction are used, they mean the up-down direction of the vehicle, the front-back direction of the vehicle, and the width direction of the vehicle, respectively.

[0074] In the present disclosure, the term "joining" means joining objects together, and bonding and welding are subordinate concepts thereof. Bonding means that two materials to be joined (materials to be joined) are joined by organic materials (curable resins, thermoplastic resins, etc.) such as tapes and adhesives. Welding means that the surfaces of thermoplastic resins, etc., which are materials to be joined, are melted by heat, and the materials are joined by entanglement and crystallization based on molecular diffusion through contact pressurization and cooling.

[0075] In the present disclosure, the term "Young's modulus" refers to a value measured for a material in accordance with JIS Z 2241:2021 "Methods for tensile testing of metallic materials." When the Young's modulus is anisotropic, the lowest value is defined as the Young's modulus of the material.

[0076] [Automotive structural parts]

[0077] As the automobile structural parts disclosed in the present invention, for example, outer panels and inner panels of a hood, door, roof, etc.; bumper reinforcements; door anti-collision beams; side beams; battery pack housings; B-pillars, etc. can be listed, but are not limited thereto.

[0078] For the purpose of presenting an exemplary method for manufacturing an automobile structural member, a method for manufacturing a bumper reinforcement will be described in detail below.

[0079] [Bumper reinforcement]

[0080] Automobiles have bumper structures at the front and rear of the vehicle. Fig. 9 As shown, the bumper structure 100, as a typical example, includes a bumper panel 10, an energy absorber 20, a bumper reinforcement 30, a crash box 40, and a vehicle body fixing member 50 in order from the front or rear of the vehicle. The bumper reinforcement 30 has a long hole 32 and a positioning hole 34 at each end. The crash box 40 has a round hole 42 for fixing the bumper reinforcement 30. The bumper reinforcement 30 and the crash box 40 are fastened by bolts 36 and nuts 46. Fig. 9 In the figure, for the purpose of visibility and simplification, the long hole and alignment hole on the lower side of the bumper reinforcement 30, as well as the bolts passing through the long hole and alignment hole and the nuts paired with the bolts are not shown. The collision energy absorbing box 40 is installed on the vehicle body fixing member 50 by means of a screw clamp or a bolt-nut (not shown). The collision energy absorbing box 40 can also be welded to the vehicle body fixing member 50 to form an integrated whole. The degree of rigidity of these components varies, and all have the performance of absorbing energy during collisions from the outside. In order to efficiently absorb impact energy, it is ideal that the bumper structure is constructed so that when it is subjected to collision energy from the outside, it is plastically deformed or destroyed in sequence starting from the components located outside the vehicle.

[0081] For example, Fig.10 As shown in FIG. 1 , when the bumper reinforcement 30 that is easily broken or excessively plastically deformed due to its light weight is arranged in the bumper structure, it is difficult for the crash box 40 to collapse when subjected to a heavy load W, and therefore the impact energy cannot be absorbed efficiently. On the other hand, in the bumper reinforcement 400 of the present disclosure, a metal reinforcement part including a metal material having a Young's modulus higher than that of the metal material of the main body by 5 GPa or more is joined to the main body constituting the bumper reinforcement 400. As a result, as shown in FIG. Fig.11 As shown, the bumper reinforcement 400 of the present disclosure will not break when subjected to a heavy load W, and can transfer the impact energy to the crash box 40 while being plastically deformed, thereby deforming the crash box 40. Therefore, the bumper structure having the bumper reinforcement 400 can efficiently absorb the impact energy.

[0082] The mass per unit length (g / m) of the bumper reinforcement can be set to less than 2700g / m, less than 2650g / m, or less than 2600g / m. There is no particular restriction on the lower limit of the mass per unit length, for example, it can be set to more than 2000g / m, more than 2100g / m, or more than 2200g / m. In one embodiment, the mass per unit length (g / m) of the bumper reinforcement is more than 2000g / m and less than 2700g / m, 2100g / m~2650g / m, or 2200g / m~2600g / m. The mass per unit length is an indicator of the lightweight of the bumper reinforcement. In the case where the bumper reinforcement is curved, for example, the unit length of the bumper reinforcement means the length in the direction in which the bumper reinforcement extends.

[0083] The residual strain of the bumper reinforcement can be set to 0.45% or less, 0.43% or less, or 0.40% or less under the conditions of a temperature of 25°C, a load of 5t, and a displacement speed of 1mm / min, and can be set to 0.20% or more, 0.25% or more, or 0.30% or more. In one embodiment, the residual strain of the bumper reinforcement is 0.20% to 0.45%, 0.25% to 0.43%, or 0.30% to 0.40%. The residual deformation is an indicator of whether the bumper reinforcement exhibits appropriate rigidity and plastic deformation.

[0084] Figure 1 A schematic perspective view showing a bumper reinforcement according to an embodiment of the present invention is shown. Figure 4 express Figure 1AA line cross-sectional view. The bumper reinforcement 400 includes a main body 200 extending in the vehicle width direction and a metal reinforcement 300 extending in the vehicle width direction. When the bumper reinforcement 400 is assembled to the bumper structure, the metal reinforcement 300 may be arranged at a position closer to the vehicle body side than the main body 200, or the main body 200 may be arranged at a position closer to the vehicle body side than the metal reinforcement 300. Figure 1 The bumper reinforcement 400 of the embodiment has a curved portion corresponding to the design of the bumper, and the metal reinforcement 300 is arranged at a position closer to the vehicle body than the main body 200. By arranging the metal reinforcement 300 at a position closer to the vehicle body than the main body 200, the plastic deformation of the main body 200 can be further promoted during a collision, and the collision energy can be absorbed efficiently.

[0085] The main body 200 and the metal reinforcement 300 constituting the bumper reinforcement are described in sequence below. The bumper reinforcement described here refers to the bumper reinforcement provided in the bumper structure (front bumper) at the front of the vehicle for ease of understanding, but the bumper reinforcement of the present disclosure can also be provided in the bumper structure (rear bumper) at the rear of the vehicle. When the bumper reinforcement of the present disclosure is used in the rear bumper, the "front part" in the following description can be replaced with the "rear part".

[0086] The length of the metal reinforcement portion 300 in the vehicle width direction can be set to be greater than 50%, greater than 55%, greater than 60%, greater than 65%, greater than 70%, greater than 75%, or greater than 85%, and less than 100%, less than 95%, less than 90%, less than 85%, less than 80%, or less than 75% of the length of the main body portion 200 in the vehicle width direction.

[0087] 〈Main body〉

[0088] Figure 2 The main body of one embodiment is shown. The main body 200 extends in the vehicle width direction and has a lower first joint 210 and an upper first joint 220. The main body 200 is gently bent at the bent portion 202 by bending processing or the like in accordance with the design of the bumper. As a result, the left and right ends of the main body 200 are located further to the rear side in the front-rear direction of the vehicle than the central portion of the main body 200. In the case of a rear bumper, the left and right ends of the main body 200 are located further to the front side in the front-rear direction of the vehicle than the central portion of the main body 200.

[0089] exist Figure 2 2 shows a case where the main body 200 has the curved portion 202 , but the main body 200 may be linear.

[0090] Long holes 270 and alignment holes 272 are provided at the left and right ends of the lower first joint 210 and the upper first joint 220 for mounting the bumper reinforcement 400 on the crash box 40 using fasteners such as bolts and nuts and screw clamps. The fasteners may be subjected to anti-electrolytic coating, surface treatment, etc. as required. In order to prevent direct contact between the bumper reinforcement 400 and the crash box 40, a resin film may be interposed between the bumper reinforcement 400 and the crash box 40 when the bumper reinforcement 400 is installed. In addition to such holes, holes for the purpose of weight reduction, release holes for releasing deformation stress caused by bending, and holes for inserting a wrench tool for bolt tightening may also be formed in the main body.

[0091] The main body 200 includes a lower portion 230, a front portion 250, and an upper portion 240 that connect the lower first joint portion 210 and the upper first joint portion 220. The front portion 250 includes a central recessed portion 252 extending in the width direction of the vehicle, a lower surface 254, and an upper surface 256. By providing the central recessed portion 252, the main body 200 can be made lighter and the rigidity of the main body 200 can be improved.

[0092] Openings 280 for mounting or positioning the energy absorber 20 such as polyurethane foam or polypropylene foam are provided at both left and right ends of the front portion 250 .

[0093] The main body 200 has a hollow structure from the viewpoint of light weight, specifically, has an open cross section. The cross-sectional shape of the main body 200 has a so-called hat-shaped form. In the present disclosure, the so-called "hat-shaped" means such as Figure 2 and Figure 4 As shown, the lower first joint portion 210 and the upper joint portion 220 extend downward and upward from the lower portion 230 and the upper portion 240, respectively, and the opposite side of the front portion 250 is open. Figure 4 The main body 200 shown has a central recessed portion 252 , so that the cross-sectional shape when rotated 90 degrees to the right is in the form of a W-shaped cap, and therefore it can also be called a W-shaped cap-shaped main body.

[0094] The size, thickness and shape of the main body 200 can be appropriately set according to the vehicle (eg, passenger car, truck, etc.) to which the bumper reinforcement is mounted and the required performance (eg, light weight, appropriate rigidity and plastic deformability).

[0095] Figure 5 A cross-sectional view showing the dimensions of the main body 200 and the metal reinforcement 300. Figure 5 The following description is not limited to the cross-sectional shape of the main body. Figure 5 Embodiment of the shape shown.

[0096] The width a1 of the upper first joint portion 220 and the width a2 of the lower first joint portion 210 are independent of each other and can be set to be 10 mm or more, 15 mm or more, 20 mm or more, or 25 mm or less, 50 mm or less, 45 mm or less, 40 mm or less, or 35 mm or less. The width of the first joint portion can be appropriately set according to the required joining force between the second joint portion of the metal reinforcement portion to be joined, etc.

[0097] The depth d1 of the upper portion 240 and the depth d2 of the lower portion 230 are independent of each other and can be set to 20 mm or more, 30 mm or more, 40 mm or more, or 50 mm or less, 100 mm or less, 90 mm or less, 80 mm or less, or 70 mm or less. The depths d1 and d2 of the upper portion 240 and the lower portion 230 can be appropriately set according to the required rigidity and plastic deformability.

[0098] The height c of the front portion 250 can be set to 50 mm or more, 60 mm or more, 80 mm or more, or 100 mm or less, or 200 mm or less, 180 mm or less, 160 mm or less, or 150 mm or less. The height c of the front portion 250 can be appropriately set according to the required rigidity and plastic deformability.

[0099] When the main body 200 is a W-shaped cap-shaped main body, the height b1 of the upper surface 256 and the height b2 of the lower surface 254 are independent of each other and can be set to be 5 mm or more, 10 mm or more, 13 mm or more, or 15 mm or less, 40 mm or less, 35 mm or less, 30 mm or less, or 25 mm or less. The depth e1 from the upper surface 256 to the central recessed portion 252 and the depth e2 from the lower surface 254 to the central recessed portion 252 are independent of each other and can be set to be 5 mm or more, 8 mm or more, 10 mm or more, or 13 mm or more, or 35 mm or less, 30 mm or less, 25 mm or less, or 20 mm or less. b1, b2, e1, and e2 can be appropriately set according to the required rigidity and plastic deformability.

[0100] The thickness t1 of the main body 200 can be set to be greater than 1.0 mm, greater than 1.5 mm, or greater than 2.0 mm, and can be set to be less than 5.0 mm, less than 4.5 mm, or less than 4.0 mm. The thickness of each part (e.g., the first joint) constituting the main body can be appropriately set according to the required performance such as light weight, appropriate rigidity and plastic deformability. The thickness of the main body 200 can be the same thickness at each part, or it can be different according to each part.

[0101] As Figure 4The angle α1 formed by the upper portion 240 and the upper first joint portion 220 in the main body 200 shown can be set to be greater than 75 degrees, greater than 80 degrees, or greater than 85 degrees, and can be set to be less than 105 degrees, less than 100 degrees, or less than 95 degrees. As the angle α1, 90 degrees is preferred. This angle can also be applied to the angle α2 formed by the lower portion 230 and the lower first joint portion 210.

[0102] The angle β1 formed by the upper surface 256 of the front part 250 and the upper part 240 can be set to 75 degrees or more, 80 degrees or more, or 85 degrees or less, 105 degrees or less, 100 degrees or less, or 95 degrees or less. The angle β1 is preferably 90 degrees. This angle can also be applied to the angle β2 formed by the lower surface 254 of the front part 250 and the lower part 230.

[0103] As the material of the main body, metal materials and metal alloy materials can be listed. Among them, iron, steel, titanium, titanium alloy, magnesium alloy, aluminum and aluminum alloy are preferred, and aluminum alloy is more preferred. These materials can be used alone or in combination of two or more.

[0104] As aluminum alloy, from the viewpoints of lightweight, appropriate rigidity and plastic deformability, it is preferred to present an aluminum alloy with a tensile strength of more than 350MPa, more than 400MPa or more than 450MPa. As the upper limit of the tensile strength of the alloy, there is no particular restriction, for example, it can be set to less than 600MPa, less than 550MPa or less than 500MPa. Here, tensile strength is the value measured using a universal testing device (AG-100KNX, Shimadzu Corporation) according to JIS Z 2241.

[0105] Examples of such aluminum alloys include alloys having an aluminum content of 50 mass % or more, specifically, A7000 series alloys (such as A7003, A7075, and A7N01), A6000 series alloys (such as A6061, A6082, and A6110), A5000 series alloys, and A3000 series alloys.

[0106] The main body may be formed of a metal material or a metal alloy material by an extruded profile, a die-cast material, a cast material, a forged material, etc. Among them, an extruded profile is preferred from the viewpoint of productivity, etc.

[0107] The extruded profile of the main body can be manufactured, for example, as follows. The following steps are performed in sequence: a step of continuously casting a cast rod by supplying a molten metal material or metal alloy material having specified characteristics to a continuous casting device; a step of homogenizing the cast rod; a step of obtaining a billet as a raw material for extrusion processing by cutting the cast rod into a specified length; a step of cutting the outer diameter surface of the billet; and a step of forming an extruded profile of a specified cross-sectional shape by water-cooling quenching immediately after hot extrusion processing the billet. Next, the extruded profile is cut into a specified length, and the two end faces after cutting are subjected to specified processing such as surface cutting and deburring processing, and a bent portion is formed by bending processing, thereby forming an extruded profile. A heat treatment process such as artificial aging treatment can be performed on the extruded profile before or after cutting the extruded profile, or before or after bending the extruded profile. For example, in the case of using A6000 series alloys and / or A7000 series alloys to form an extruded profile, such a heat treatment process is preferably performed.

[0108] 〈Metal reinforcement〉

[0109] Figure 3 The figure shows a metal reinforcement part of an embodiment. The metal reinforcement part 300 has at least one second joint part extending in the vehicle width direction. In the case of this figure, the metal reinforcement part 300 has a lower second joint part 310 and an upper second joint part 320 as the second joint part. When the metal reinforcement part 300 has two second joint parts, namely, the lower second joint part 310 and the upper second joint part 320, it is preferably provided with a reinforcement part body 304.

[0110] The reinforcement body 304 is in the shape of a plate with the vehicle width direction as the length direction, the vehicle up-down direction as the width direction, and the vehicle front-back direction as the thickness direction, and has a bent portion 302 at a position corresponding to the bent portion 202 of the main body 200. The reinforcement body 304 has a lower second joint portion 310 and an upper second joint portion 320 integrally formed at the lower and upper sides of the main body side surface, respectively.

[0111] exist Figure 3 3 shows a case where the reinforcing portion main body 304 has the bent portion 302 , but when the main body 200 is in a straight line shape, the reinforcing portion main body 304 may also be in a straight line shape.

[0112] The lower second joint part 310 is a strip-shaped area extending from one end to the other end in the vehicle width direction and having a predetermined width, which is arranged on the lower side of the reinforcement body 304. The upper second joint part 320 is a strip-shaped area extending from one end to the other end in the vehicle width direction and having a predetermined width, which is arranged on the upper side of the reinforcement body 304. The widths of the lower second joint part 310 and the upper second joint part 320 are selected according to the length of the first joint part in the vehicle up-down direction. In this way, the lower second joint part 310 and the upper second joint part 320 cover the entire area in the length direction of the reinforcement body 304. The lower second joint part 310 and the upper second joint part 320 are integrated through the reinforcement body 304. The lower second joint part 310 and the upper second joint part 320 are joined in a state of contacting the lower first joint part 210 and the upper first joint part 220 on the surface of the main body side.

[0113] like Figure 1 and Figure 4 As shown, the lower second joint part 310 and the upper second joint part 320 of the metal reinforcement part 300 are respectively joined to the lower first joint part 210 and the upper first joint part 220 of the main body part. The lower second joint part 310 and the upper second joint part 320 are joined to the lower first joint part 210 and the upper first joint part 220 at a joint surface intersecting the front-rear direction of the vehicle. The main body 200 has an open cross section, and the lower first joint part 210 and the upper first joint part 220 of the main body 200 and the lower second joint part 310 and the upper second joint part 320 of the metal reinforcement part 300 are respectively joined in a manner such that a cavity 260 is formed inside the main body 200.

[0114] exist Figure 1 In the embodiment, the length of the metal reinforcement 300 in the vehicle width direction is the same as the length of the main body 200 in the vehicle width direction, that is, 100% of the length of the main body 200 in the vehicle width direction, and the metal reinforcement 300 is provided with a long hole 370 and an alignment hole 372 at positions corresponding to the long hole 270 and the alignment hole 272 of the main body 200. In this embodiment, the periphery of the long hole 370 and the alignment hole 372 of the metal reinforcement 300 functions as a high-strength mounting part, so that the bumper reinforcement 400 can be mounted to the crash box 40 with high strength. In addition, when the ionization tendency of the material of the crash box 40 and the material of the metal reinforcement 300 are similar, even if the crash box 40 and the metal reinforcement 300 are in contact, it is difficult for electric corrosion to occur. Therefore, according to this embodiment, the metal reinforcement 300 isolates the body 200 from the crash box 40 , and the risk of electric corrosion occurring at the attachment portion of the bumper reinforcement 400 to the crash box 40 can be reduced.

[0115] The size, thickness and shape of the metal reinforcement 300 can be appropriately set according to the vehicle (eg, passenger car, truck, etc.) to which the bumper reinforcement is mounted and the required performance (eg, light weight, appropriate rigidity and plastic deformability).

[0116] The width h1 of the upper second joint portion 320 and the width h2 of the lower second joint portion 310 are independent of each other and can be set to be 10 mm or more, 15 mm or more, 20 mm or more, or 25 mm or less, 50 mm or less, 45 mm or less, 40 mm or less, or 35 mm or less. The width of the second joint portion can be appropriately set according to the required joint force between the first joint portion of the main body to be joined, etc.

[0117] The thickness t2 of the metal reinforcement can be set to be greater than 0.2 mm, greater than 0.3 mm, or greater than 0.4 mm, and can be set to be less than 2.0 mm, less than 1.5 mm, or less than 1.0 mm. The thickness of each part (e.g., the reinforcement body, the first joint part, and the second joint part) constituting the metal reinforcement can be appropriately set according to the required performance such as light weight, appropriate rigidity, and plastic deformability. The thickness of the metal reinforcement 300 can be the same thickness at each part, or it can be different according to each part.

[0118] Figure 3 The metal reinforcement 300 shown has four holes (lightweight holes (weight-reducing holes)) 350 near the center. By providing the lightweight holes, the metal reinforcement can be made lighter. There can be more than one hole, and the number, size and shape of the holes can be appropriately set according to the required performance (e.g., lightness, appropriate rigidity and plastic deformability).

[0119] As the material of the metal reinforcement, metal materials and metal alloy materials can be listed. The Young's modulus of the material of the metal reinforcement is higher than that of the material of the main body by more than 5 GPa. The Young's modulus of the material of the metal reinforcement is preferably higher than that of the material of the main body by more than 30 GPa, more preferably higher than that of 50 GPa, and further preferably higher than that of 80 GPa. In one embodiment, the Young's modulus of the material of the metal reinforcement is higher than that of the material of the main body by 5 GPa to 180 GPa, 30 GPa to 170 GPa, 50 GPa to 160 GPa, or 80 GPa to 150 GPa. As the material of the metal reinforcement, iron, steel, titanium, titanium alloy, aluminum and aluminum alloy are preferred, and iron, steel and aluminum alloys with high strength and high rigidity (such as Al-Si aluminum alloy and Al-Zn aluminum alloy) are more preferred. These materials can be used alone or in combination of two or more.

[0120] Regarding the Young's modulus of the metal materials and metal alloy materials used in the main body and the metal reinforcement, for example, it is known that the aluminum alloy A6061-T6 is 68.3 GPa, the steel plate of 440 MPa grade steel is 203 GPa, the stainless steel SUS304 is 197 GPa, the high-rigidity aluminum alloy A4032-T6 is 79 GPa, and the titanium alloy Ti-6 Al-4 V is 106 GPa.

[0121] The metal reinforcement portion can be formed by processing a plate-shaped metal material or metal alloy material using a known processing method such as press processing, laser processing, shearing processing, bending processing, cutting processing, etc.

[0122] [Manufacturing method of automobile structural parts (joined bodies)]

[0123] A method for manufacturing an automobile structural part according to one embodiment includes a pre-joining step and a joining step.

[0124] In the pre-joining step, a laminated body is formed in which a first metal member, a solid bonding agent, and a second metal member to be joined to the first metal member are sequentially arranged, the solid bonding agent contains an amorphous thermoplastic resin as a main component, and the amorphous thermoplastic resin is at least one of a thermoplastic epoxy resin and a phenoxy resin;

[0125] In the bonding step, the stacked body is heated and pressurized to melt the solid bonding agent, thereby bonding the first metal member and the second metal member.

[0126] In the pre-joining process, the first metal component and the solid bonding agent, and the second metal component and the solid bonding agent are not joined, but joined in a subsequent joining process. The solid bonding agent may also be viscous, in which case the solid bonding agent is temporarily fixed to the substrate in the pre-joining process.

[0127] The Young's modulus of the second metal component is higher than that of the first metal component by more than 5 GPa. As one of the functions of general automotive structural parts, it can be listed that when a force is applied from the outside such as a collision, the energy is absorbed while the shape of the automotive structural parts is maintained for as long as possible, so that the automotive parts remain in a specified position. The energy absorption of automotive structural parts formed only with materials with high Young's modulus is insufficient. On the other hand, the shape retention of automotive structural parts formed only with materials with low Young's modulus is low. As disclosed in the present invention, an automotive structural part formed by combining metal materials with different Young's moduli can realize the functions of both energy absorption and shape retention in the entire automotive structural part by having a part showing energy absorption (low Young's modulus material) and a part showing shape retention (high Young's modulus material) in one structural part. In the case where the difference between the Young's modulus of the second metal component and the Young's modulus of the first metal component is less than 5 GPa, the above-mentioned benefit generated by combining materials with different Young's moduli is small, and the advantages compared with the structural parts formed integrally with one material cannot be obtained. The Young's modulus of the second metal member is preferably higher than the Young's modulus of the first metal member by 10 GPa or more, more preferably higher than 20 GPa or more, and further preferably higher than 30 GPa or more. In one embodiment, the Young's modulus of the second metal member is higher than the Young's modulus of the first metal member by 5 GPa to 180 GPa, 10 GPa to 170 GPa, 20 GPa to 160 GPa, or 30 GPa to 150 GPa.

[0128] In an embodiment where the automobile structural part is a bumper reinforcement 30, the first metal component is the main body extending in the vehicle width direction and having at least one first joint. The second metal component is the metal reinforcement extending in the vehicle width direction and having at least one second joint. The first joint of the main body and the second joint of the metal reinforcement are bonded by a solid bonding agent. The metal reinforcement may be arranged at a position closer to the vehicle body than the main body, or the main body may be arranged at a position closer to the vehicle body than the metal reinforcement.

[0129] 〈Pre-joining process〉

[0130] In the pre-bonding process, a laminated body is formed in which a first metal member, a solid bonding agent, and a second metal member are sequentially arranged, wherein the solid bonding agent is mainly composed of an amorphous thermoplastic resin, and the amorphous thermoplastic resin is at least one of a thermoplastic epoxy resin and a phenoxy resin. In the laminated body, the first metal member and the solid bonding agent, and the solid bonding agent and the second metal member are not bonded to each other, and are in a state where the independent members are overlapped.

[0131] The solid adhesive is solid at room temperature, that is, has no fluidity in an unpressurized state at 23° C. The solid adhesive preferably has the property of not deforming and maintaining its shape for more than 30 days in an unpressurized state at 23° C. and not deteriorating.

[0132] The above-mentioned "main component" is the component with the highest content among the resin components in the solid adhesive, and refers to the component whose content in the resin components in the solid adhesive is 50% by mass or more. The solid adhesive preferably contains 50% by mass or more of the resin component, more preferably 70% by mass or more of the resin component, further preferably 80% by mass or more of the resin component, and particularly preferably 90% by mass or more of the resin component.

[0133] (Solid adhesive)

[0134] The solid bonding agent has an amorphous thermoplastic resin as a main component, and the amorphous thermoplastic resin is at least one of a thermoplastic epoxy resin and a phenoxy resin. In the previous bonding using a liquid adhesive, bubbles may be mixed into the bonding portion, or the bonded metal components may contact each other when there are bumps and depressions on the surface of the metal components. The mixing of bubbles into the bonding portion or the contact between the metal components may cause galvanic corrosion between dissimilar metal components. In the present disclosure, by using a solid bonding agent having an amorphous thermoplastic resin as a main component, which is at least one of a thermoplastic epoxy resin and a phenoxy resin, the mixing of bubbles can be prevented, and the metal components can be bonded to each other while absorbing the bumps and depressions on the surface of the metal components with the thickness of the solid bonding agent. Therefore, according to the present disclosure, it is possible to prevent the contact between the metal components and suppress the galvanic corrosion that may occur between the dissimilar metal components.

[0135] The amorphous resin in the present disclosure refers to a resin that has a melting point (Tm) but does not have an endothermic peak (melting point) associated with clear melting or has a very small endothermic peak in the measurement using a differential scanning calorimeter (DSC). The heat of fusion is calculated based on the area of ​​the endothermic peak of DSC and the mass of the thermoplastic resin component. When an inorganic filler or the like is contained in the solid adhesive, the heat of fusion is calculated based on the mass of the resin component excluding the inorganic filler.

[0136] In one embodiment, the so-called amorphous thermoplastic resin refers to a resin having properties measured by the following steps. A sample of 2 to 10 mg is weighed and placed in an aluminum pan, and the temperature is raised from 23°C to 200°C or higher at 10°C / min using DSC (DSC8231 manufactured by Rigaku Corporation) to obtain a DSC curve. Next, when the heat of fusion is calculated based on the area of ​​the endothermic peak during melting obtained from the DSC curve and the above-mentioned weighed value, a resin having a heat of fusion of 15 J / g or less is considered to be an amorphous thermoplastic resin.

[0137] From the perspective of sufficiently imparting the properties of the amorphous thermoplastic resin to the solid adhesive, the content of the amorphous thermoplastic resin in the resin component in the solid adhesive is preferably 60 mass % or more, more preferably 70 mass % or more, further preferably 80 mass % or more, and most preferably 90 mass % or more.

[0138] The heat of fusion is preferably 15 J / g or less, more preferably 11 J / g or less, further preferably 7 J / g or less, particularly preferably 4 J / g or less, and most preferably the melting peak is below the detection limit.

[0139] The epoxy equivalent is preferably 1,600 or more, more preferably 2,000 or more, further preferably 5,000 or more, particularly preferably 9,000 or more, and most preferably it is equal to or more than the detection limit and substantially no epoxy group is detected.

[0140] In one embodiment, by using a solid adhesive having an epoxy equivalent of 1600 or more and a non-crystalline thermoplastic resin as the main component and a heat of fusion of 15 J / g or less, when heated, the viscosity does not drop sharply as seen in conventional hot melt adhesives, and the low viscosity (0.001 to 100 Pa·s) state is not reached even in a high temperature range exceeding 200°C. Therefore, the solid adhesive does not flow out of the laminate even in a molten state, and the thickness of the adhesive layer can be stably ensured. As a result, contact between metal components can be more reliably prevented, thereby preventing electrolytic corrosion, and a high adhesive force can be stably obtained. The epoxy equivalent (the mass of the above-mentioned resin containing 1 mol of epoxy groups) in the present disclosure is the value of the epoxy equivalent of the thermoplastic epoxy resin or phenoxy resin component contained in the solid adhesive before bonding, and is a value measured by the method specified in JIS K7236:2001 (unit "g / eq."). Specifically, the epoxy equivalent of the resin is measured using a potentiometric titration apparatus, cyclohexanone as a solvent, tetraethylammonium bromide acetic acid solution is added to the resin, and a 0.1 mol / L perchloric acid-acetic acid solution is used. For solvent-diluted products (resin varnishes), the value calculated as a solid content conversion value is calculated based on the non-volatile component. The epoxy equivalent of a mixture of two or more resins can also be calculated from the content and epoxy equivalent of each resin.

[0141] The melting point of the amorphous thermoplastic resin as the main component of the solid adhesive is preferably 50 to 400°C, more preferably 60 to 350°C, and even more preferably 70 to 300°C. When the melting point is in the range of 50 to 400°C, the solid adhesive is efficiently deformed and melted by heating, thereby effectively wetting and spreading on the bonding surface, thereby obtaining a high adhesive force. In the present disclosure, the melting point of the amorphous thermoplastic resin means the temperature at which the solid is substantially softened and becomes thermoplastic, and becomes meltable and bondable.

[0142] In conventional joints containing thermosetting adhesives, it is difficult to disassemble the joint and to separate the dissimilar materials constituting the joint for recycling (i.e., poor recyclability). In addition, when a thermosetting adhesive is used, it is difficult to re-paste when there is an offset of the joining portion during the manufacturing process of the joint, or when the joined objects have defects and need to be replaced (i.e., poor repairability), which lacks convenience. On the other hand, the above-mentioned solid adhesive can be softened and melted by heat, and can easily separate the two joined objects, so it has excellent recyclability. In addition, the above-mentioned solid adhesive is thermoplastic, and therefore can be reversibly softened, melted, and hardened (cured) repeatedly, and it also has excellent repairability.

[0143] Thermoplastic Epoxy Resin

[0144] The thermoplastic epoxy resin is preferably a polymer of (a) a difunctional epoxy resin monomer or oligomer and (b) a difunctional compound having two identical or different functional groups selected from phenolic hydroxyl, carboxyl, mercapto, isocyanate and cyanate groups. By using this compound, the polymerization reaction to form a linear polymer is preferentially carried out, and a thermoplastic epoxy resin having desired properties can be formed.

[0145] The (a) bifunctional epoxy resin monomer or oligomer refers to an epoxy resin monomer or oligomer having two epoxy groups in the molecule. Examples of the (a) difunctional epoxy resin monomer or oligomer include bisphenol A type epoxy resin, bisphenol F type epoxy resin, difunctional phenol novolac type epoxy resin, bisphenol AD ​​type epoxy resin, biphenyl type epoxy resin, difunctional naphthalene type epoxy resin, difunctional alicyclic epoxy resin, difunctional glycidyl ester type epoxy resin (e.g. diglycidyl phthalate, diglycidyl tetrahydrophthalate, diglycidyl dimer acid diglycidyl ester, etc.), difunctional glycidyl amine type epoxy resin (e.g. diglycidyl aniline, diglycidyl toluidine, etc.), difunctional heterocyclic epoxy resin, difunctional diaryl sulfone type epoxy resin, hydroquinone type epoxy resin (e.g. hydroquinone diglycidyl ether, 2, diglycidyl ether, 1,3-bis(3-glycidyloxypropyl)-1,1,3,3-tetramethyldisiloxane, α,β-bis(3-glycidyloxypropyl)polydimethylsiloxane, and their modified products. Among them, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin and biphenyl type epoxy resin are preferred from the viewpoint of reactivity and handleability.

[0146] Examples of the bifunctional compound having a phenolic hydroxyl group of (b) include mononuclear aromatic dihydroxy compounds having one benzene ring such as catechol, resorcinol, and hydroquinone, bisphenol compounds such as bis(4-hydroxyphenyl)propane (bisphenol A), bis(4-hydroxyphenyl)methane (bisphenol F), and bis(4-hydroxyphenyl)ethane (bisphenol AD), compounds having a condensed ring such as dihydroxynaphthalene, bifunctional phenol compounds into which an allyl group is introduced such as diallylresorcinol, diallylbisphenol A, and triallyldihydroxybiphenyl, and dibutylbisphenol A.

[0147] Examples of the bifunctional compound having a carboxyl group (b) include adipic acid, succinic acid, malonic acid, cyclohexanedicarboxylic acid, phthalic acid, isophthalic acid, and terephthalic acid.

[0148] Examples of the bifunctional compound having a mercapto group (b) include ethylene glycol bis(thioglycolate) and ethylene glycol bis(thiopropionate).

[0149] Examples of the difunctional compound having an isocyanate group (b) include diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HMDI), and benzal diisocyanate (TDI).

[0150] Examples of the bifunctional compound having a cyanate group (b) include 2,2-bis(4-cyanophenyl)propane, 1,1-bis(4-cyanophenyl)ethane, and bis(4-cyanophenyl)methane.

[0151] In the above (b), from the viewpoint of being able to form a thermoplastic polymer with very suitable properties, a difunctional compound having a phenolic hydroxyl group is preferred, from the viewpoint of heat resistance and adhesion, a difunctional compound having two phenolic hydroxyl groups and a bisphenol structure or a biphenyl structure is preferred, and from the viewpoint of heat resistance and cost, bisphenol A, bisphenol F and bisphenol S are preferred.

[0152] In the case where (a) is a bisphenol A epoxy resin, a bisphenol F epoxy resin, a bisphenol S epoxy resin or a biphenyl epoxy resin, and (b) is bisphenol A, bisphenol F or bisphenol S, the polymer obtained by polymerization of (a) and (b) has a main chain with a paraphenylene structure and an ether bond as the main skeleton and they are connected by an alkylene group, and has a structure in which a hydroxyl group generated by addition polymerization is arranged on the side chain. The mechanical strength of the polymer after polymerization can be improved by the linear structure of the main skeleton having a paraphenylene structure and an ether bond, and the adhesion to the substrate can be improved by the hydroxyl group arranged on the side chain. As a result, the workability can be maintained and the high bonding strength at the same level as that of a thermosetting resin can be achieved. Moreover, by using heat to soften and melt it, it can be recycled and repaired, and the recyclability and repairability that are the problems of thermosetting resins can be improved.

[0153] Phenoxy resin

[0154] Phenoxy resin is a polyhydroxy polyether synthesized from bisphenol compounds and epichlorohydrin, and has thermoplasticity. As a method for manufacturing phenoxy resin, a method based on the direct reaction of diphenol compounds and epichlorohydrin, and a method based on the addition polymerization of diglycidyl ether of diphenol compounds and diphenol compounds are known, but phenoxy resin can be obtained by any method. In the case of direct reaction of diphenol compounds and epichlorohydrin, as diphenol compounds, for example, phenol compounds such as bisphenol A, bisphenol F, bisphenol S, biphenol, biphenylene diol, and fluorene biphenyl can be listed. Among them, from the viewpoint of cost, adhesion, viscosity and heat resistance, bisphenol A, bisphenol F and bisphenol S are preferred. In addition to diphenol compounds, aliphatic diols such as ethylene glycol, propylene glycol, and diethylene glycol can also be contained in the above-mentioned direct reaction. They can be used alone or in combination of two or more. The phenoxy resin has a chemical structure similar to that of the epoxy resin, and has a main chain having a p-phenylene structure and an ether bond as a main skeleton and connected thereto, and a structure in which a hydroxyl group is arranged in a side chain.

[0155] Thermoplastic epoxy resin and phenoxy resin

[0156] The weight average molecular weight of the above-mentioned thermoplastic epoxy resin and phenoxy resin is preferably 10000-500000, more preferably 18000-300000, and further preferably 20000-200000, according to the value of polystyrene conversion measured based on GPC (gel permeation chromatography). The weight average molecular weight is a standard polystyrene conversion value calculated from the dissolution peak position detected by GPC. When the weight average molecular weight is the above range, the balance of thermoplasticity and heat resistance is good, so it is possible to efficiently form a joint body by melting, and it is also possible to improve the heat resistance of the joint body. When the weight average molecular weight is more than 10000, the heat resistance is excellent, and when it is less than 500000, the viscosity during melting is low, and the adhesion becomes high.

[0157] Method for producing solid bonding agent

[0158] The method for producing the solid adhesive is not particularly limited, and it can be obtained, for example, by heating a monomer or oligomer of a bifunctional epoxy compound to polymerize it. In order to reduce the viscosity during polymerization and facilitate stirring, a solvent may also be added. When a solvent is added, it is necessary to remove it, and the solid adhesive can be obtained by drying or polymerizing or both on a release film or the like.

[0159] Other additives may be added to the solid adhesive as needed within a range that does not impair the effects of the present invention. The amount of additives added relative to the total amount of the amorphous thermoplastic resin is preferably 50% by volume or less, more preferably 30% by volume or less, further preferably 20% by volume or less, and most preferably 10% by volume or less. In the present disclosure, the volume % of the additives refers to the volume ratio of the additives contained before the polymerization of the monomer or oligomer of the bifunctional epoxy compound based on the volume of the total amount of the amorphous thermoplastic resin, and the volume of the additives can be obtained by dividing the mass of the additives contained by the true specific gravity of the additives.

[0160] Examples of the additives include viscosity modifiers, inorganic fillers, organic fillers (resin powders), defoamers, coupling agents such as silane coupling agents, and pigments. These additives may be used alone or in combination of two or more. Examples of the viscosity modifier include reactive diluents. Examples of the inorganic filler include spherical fused silica, metal powders of metals such as iron, silica sand, talc, calcium carbonate, mica, acid clay, diatomaceous earth, kaolin, quartz, titanium oxide, silicon dioxide, phenolic resin microballoons, and glass balloons.

[0161] The solid adhesive thus obtained has a low content of unreacted monomers or terminal epoxy groups, or contains substantially no unreacted monomers or terminal epoxy groups, and therefore has excellent storage stability and can be stored for a long period of time at room temperature.

[0162] The form of the solid adhesive before melting is not particularly limited, but it is preferably any one of a film, a rod, a particle and a powder, and more preferably a film. The solid adhesive in the form of a film can join the metal components to be joined while firmly holding them at a predetermined interval throughout the entire joining surface. Therefore, the solid adhesive in the form of a film is particularly useful for preventing electrolytic corrosion. The thickness of the solid adhesive in the form of a film is preferably 10 μm to 5 mm, more preferably 20 μm to 3 mm, and further preferably 30 μm to 0.5 mm. By making the thickness of the solid adhesive in the form of a film more than 10 μm, electrolytic corrosion between the first metal component and the second metal component can be more effectively prevented, and the bonding strength can be ensured. By making the thickness of the solid adhesive in the form of a film less than 5 mm, the bonding strength in the shear direction of the joining surface can be increased.

[0163] The solid adhesive may have viscosity within a range that does not impair the adhesive force and heat resistance. In this case, the solid adhesive can be temporarily fixed to the substrate in the laminate preparation step.

[0164] 〈Joining process〉

[0165] In the bonding step, the stacked body is heated and pressurized to melt the solid bonding agent, and then the temperature is lowered to solidify the solid bonding agent, thereby bonding the first metal member and the second metal member.

[0166] The temperature during the above heating and pressurizing is preferably 100°C or more, more preferably 120°C or more, and further preferably 150°C or more. The temperature during the above heating and pressurizing is preferably 400°C or less, more preferably 350°C or less, and further preferably 300°C or less. Any combination of these lower limits and upper limits may be used. The temperature during the above heating and pressurizing is preferably 100 to 400°C, more preferably 120 to 350°C, and further preferably 150 to 300°C. By heating at a temperature of 100 to 400°C, the above solid adhesive is efficiently deformed and melted, and effectively wets and spreads on the bonding surface, so that a high bonding force can be obtained.

[0167] The pressure during the above heating and pressurizing is preferably 0.01 MPa or more, more preferably 0.1 MPa or more, and further preferably 0.2 MPa or more. The pressure during the above heating and pressurizing is preferably 20 MPa or less, more preferably 10 MPa or less, and further preferably 5 MPa or less. The combination of these lower limit values ​​and upper limit values ​​can be any combination. The pressure during the above heating and pressurizing is preferably 0.01 to 20 MPa, more preferably 0.1 to 10 MPa, and further preferably 0.2 to 5 MPa. The pressure here refers to the average pressure at the joint surface of the first metal component and the second metal component. If it is in such a pressure range, the above solid adhesive is efficiently deformed and effectively wets and expands on the joint surface, so that a high bonding force can be obtained.

[0168] Thermoplastic epoxy resin and phenoxy resin, which are main components of solid adhesives, have low cohesive force in the resin and have hydroxyl groups, so they interact strongly with the substrate and can bond dissimilar materials with higher adhesive strength than conventional crystalline hot melt adhesives.

[0169] The bonding between the first metal component and the second metal component utilizes the phase change (solid-liquid-solid) of the solid bonding agent and is not accompanied by a chemical reaction. Therefore, the bonding can be completed in a shorter time compared to conventional thermosetting epoxy resins.

[0170] The thickness of the solid adhesive after joining is preferably 10 μm to 5 mm, more preferably 20 μm to 3 mm, and further preferably 30 μm to 0.5 mm. By setting the thickness of the solid adhesive after joining to be 10 μm or more, it is possible to more reliably prevent electrolytic corrosion between the first metal member and the second metal member, and ensure bonding strength. By setting the thickness of the solid adhesive after joining to be 5 mm or less, it is possible to increase the bonding strength in the shear direction of the joining surface, and further improve the shape retention of the automotive structural parts.

[0171] [Bumper reinforcement 30 (joined body)]

[0172] Fig.12 is a schematic cross-sectional view showing a state where the first metal member 2 and the second metal member 5 are bonded together by a solid bonding agent, and is a view showing, for example, Figure 1 and Figure 4 The diagram shows the joining portion between the lower first joining portion 210 (equivalent to the first metal component 2) of the main body 200 and the lower second joining portion 310 (equivalent to the second metal component 5) of the metal reinforcement portion 300, or the joining portion between the upper first joining portion 220 (equivalent to the first metal component 2) of the main body 200 and the upper second joining portion 320 (equivalent to the second metal component 5) of the metal reinforcement portion 300.

[0173] exist Fig.12 In the joint shown, the first metal component 2 and the second metal component 5 are joined and integrated by the adhesive layer 3. The adhesive layer 3 is a solid adhesive agent whose main component is an amorphous thermoplastic resin as at least one of a thermoplastic epoxy resin and a phenoxy resin, which is melted and solidified. The joint of the first metal component 2 and the second metal component 5 shows excellent bonding strength. In addition to being affected by the strength of the interface interaction between the adhesive layer and the substrate, the bonding strength is also affected by many factors such as the thickness of the adhesive layer, the molecular weight and chemical structure of the polymer constituting the adhesive, mechanical properties, and viscoelastic properties. Therefore, the details of the mechanism by which the joint of the present invention shows excellent bonding strength are not yet clear, but it is speculated that: the cohesive force of the amorphous thermoplastic resin constituting the adhesive layer 3 is low, hydroxyl groups exist in the resin, and hydrogen bonds, van der Waals forces, and other chemical bonds or intermolecular forces are formed at the interface between the adhesive layer and the first metal component 2 and the interface between the adhesive layer and the second metal component 5. However, in a bonded body, the state or characteristics of the interface of the bonded body are caused by an extremely thin chemical structure with a thickness of less than nanometer level, and therefore analysis is difficult. It is impossible or impractical with current technology to determine the state or characteristics of the interface of the bonded body of the present invention so as to distinguish it from a bonded body that does not contain the solid bonding agent of the present invention.

[0174] The automobile structural part of the present disclosure, in which the adhesive layer comprises an amorphous thermoplastic resin, has excellent recyclability and repairability, and can be easily disassembled into the first metal component 2 and the second metal component 5 by heating the joint body. For example, in the case of a bumper reinforcement, it can be easily disassembled into the main body 200 and the metal reinforcement 300.

[0175] Sometimes, high bonding strength can be obtained by performing appropriate pretreatment on the first metal component 2 or the second metal component 5 or both. As the pretreatment, it is preferred to perform a pretreatment on the surface of the substrate by cleaning it or to perform a pretreatment on the surface by giving it a concave-convex shape. The pretreatment may be only one, or two or more may be performed. As specific methods of these pretreatments, known methods can be used.

[0176] The pretreatment of the first metal member 2 and the second metal member 5 is preferably at least one selected from the group consisting of a degreasing treatment, a UV ozone treatment, a sandblasting treatment, a grinding treatment, a plasma treatment, and an etching treatment.

[0177] [Function and Effect]

[0178] like Figure 4 As shown, the action and effect of the bumper reinforcement are described by taking the case where the bumper reinforcement bears a heavy load W in the front-to-back direction of the vehicle as an example. First, the force generated by the heavy load W is applied to the front portion 250 of the main body 200. The force is transmitted from the front portion 250 to the lower first joint portion 210 and the upper first joint portion 220 through the lower portion 230 and the upper portion 240. Since the main body 200 is a hat-shaped, the above-mentioned force is dispersed into a force F1 in the front-to-back direction of the vehicle for the metal reinforcement 300, and is dispersed into a force F2 in the direction along the joint surface (in the direction of the joint surface) for the lower first joint portion 210 and the upper first joint portion 220. Figure 4 In the case of , the outward force F2 is transmitted respectively in the up and down directions of the vehicle.

[0179] The lower second joint part 310 and the upper second joint part 320 are joined to the lower first joint part 210 and the upper first joint part 220 at a joint surface intersecting the front-rear direction of the vehicle. That is, the force F2 is propagated on the joint surface. The force F2 is smaller than the heavy load W by an amount corresponding to the amount of force F1 dispersed among the forces generated by the heavy load W. Therefore, compared with the case where the lower second joint part 310 and the upper second joint part 320 and the lower first joint part 210 and the upper first joint part 220 are provided with a joint surface parallel to the front-rear direction of the vehicle, the joint strength can be significantly improved.

[0180] The lower first joint portion 210 and the upper first joint portion 220 are respectively joined to the lower second joint portion 310 and the upper second joint portion 320, and the lower second joint portion 310 and the upper second joint portion 320 are formed integrally with the reinforcement body 304. Therefore, the metal reinforcement 300 exerts stress against the force F2. That is, the reinforcement body 304 exerts stress against the force F2. Thus, the metal reinforcement 300 suppresses the lower first joint portion 210 and the upper first joint portion 220 of the main body 200 from deforming outward in the vehicle vertical direction.

[0181] In addition, the heavy load W generates a force that bends the bumper reinforcement 400 in the vehicle width direction. The lower second joint portion 310 and the upper second joint portion 320 of the metal reinforcement 300 are respectively joined to the lower first joint portion 210 and the upper first joint portion 220 of the main body 200 over the entire area in the vehicle width direction. Thus, the metal reinforcement 300 can maintain the state of being joined to the main body 200, and the metal reinforcement 300 exerts stress against the force of bending in the vehicle width direction. Thus, the metal reinforcement 300 suppresses the main body 200 from bending in the vehicle width direction.

[0182] Therefore, the bumper reinforcement 400 can absorb the force generated by the heavy load W through plastic deformation of the main body 200 and the metal reinforcement 300, and effectively transmit the impact energy that is not completely absorbed to the crash box. As a result, the vehicle equipped with the bumper reinforcement 400 can effectively transmit the impact energy generated by the heavy load W to the crash box 40 and absorb the impact energy efficiently, thereby suppressing damage to the vehicle body.

[0183] <Modification 1: Modification 1 of bumper reinforcement>

[0184] Figure 6 A cross-sectional view of a bumper reinforcement according to another embodiment is shown. The bumper reinforcement has a main body 500 and a metal reinforcement 600. The materials and thicknesses of the main body 500 and the metal reinforcement 600, the angles of the reinforcement ribs 620 in the metal reinforcement 600, etc., can be similarly adopted to those described in the main body 200 and the metal reinforcement 300 described above.

[0185] The opposite side of the front face 550 of the main body 500 is closed, and the closed portion constitutes the first joining portion 510. That is, the main body 500 has a closed cross-section, and such a main body is sometimes referred to as a "closed type main body" in the present disclosure. The metal reinforcement 600 has a reinforcement body 602 and a second joining portion 610 extending along the width direction of the vehicle. The reinforcement body 602 is a plate with the vehicle width direction as the length direction, the vehicle up and down direction as the width direction, and the vehicle front and rear direction as the thickness direction. The reinforcement body 602 and the second joining portion 610 are integral. The second joining portion 610 is joined to the first joining portion 510 over the entire surface of the reinforcement body 602 on the main body side. The second joining portion 610 of the metal reinforcement 600 is joined to the first joining portion 510.

[0186] (Closed body)

[0187] In the closed body 500, two hollow portions 560 are formed with the middle portion 520 as a boundary. The number of the hollow portions of the closed body is not particularly limited, and can be appropriately selected in consideration of lightness, appropriate rigidity, and plastic deformability, but preferably two or more hollow portions are formed. For example, in the case where three hollow portions are formed, there will be two middle portions 520.

[0188] exist Figure 6 In the embodiment, the outer cross-sectional shape of the main body 500 is a rectangle. The outer cross-sectional shape of the closed main body is not particularly limited, and may be a triangle, a square, a trapezoid, a semicircle, or the like.

[0189] Figure 7 A cross-sectional view showing the dimensions of the main body 500 and the metal reinforcement 600. Figure 7 The following description is not limited to the cross-sectional shape of the main body. Figure 7 Embodiment of the shape shown.

[0190] The height i1 of the front portion 550 and the width j of the first joint portion 510 are independent of each other and can be set to be 50 mm or more, 60 mm or more, 80 mm or more, or 100 mm or less, 200 mm or less, 180 mm or less, 160 mm or less, or 150 mm or less. The height i1 of the front portion 550 and the width j of the first joint portion 510 can be appropriately set according to the required performance (joint strength, rigidity, and plastic deformability).

[0191] The depth i2 of the main body 500 may be set to be greater than 20 mm, greater than 30 mm, greater than 40 mm, or greater than 50 mm, and may be less than 100 mm, less than 90 mm, less than 80 mm, or less than 70 mm. The depth i2 of the main body 500 may be appropriately set according to the required rigidity and plastic deformability.

[0192] The height i3 of the cavity 560 can be set to be greater than 20 mm, greater than 30 mm, greater than 40 mm, or greater than 50 mm, and can be set to be less than 100 mm, less than 90 mm, less than 80 mm, or less than 70 mm. The height i3 of the cavity 560 can be appropriately set according to the required rigidity and plastic deformability.

[0193] The thickness t3 of the main body 500 can be set to the same range as the thickness t1 of the main body 200 .

[0194] (Metal reinforcement)

[0195] Figure 6 The width of the second joint k1 of the metal reinforcement 600 (equivalent to the height of the metal reinforcement) is in the same range as the width j of the first joint 510, or may be different from the width j of the first joint 510. The thickness t4 of the metal reinforcement 600 may be in the same range as the thickness t2 of the metal reinforcement 300.

[0196] Although the manufacturing method of the bumper reinforcement is described by way of example, the manufacturing method of the automobile structural parts disclosed in the present invention can be applied to the manufacture of outer panels and inner panels of the engine hood, door, roof, etc., in which the above-mentioned first metal component and the above-mentioned second metal component are joined by the above-mentioned solid adhesive; door anti-collision beams; side beams; battery pack shells; and other automobile structural parts such as B-pillars.

[0197] Example

[0198] Examples, comparative examples, implementation test examples, and comparative test examples related to the present invention are shown below, but the present invention is not limited thereto. In the following examples, the first metal member and the second metal member are collectively referred to as a bonding substrate.

[0199] 〈Bonding base material〉

[0200] The following bonding substrates were used.

[0201] Steel Plate

[0202] The surface of 440 MPa grade high strength cold rolled steel sheet JFE-CA440 for automobile outer panels (manufactured by JFE Steel Corporation, Young's modulus 203 GPa) was sandblasted to obtain a test piece having a width of 10 mm, a length of 45 mm, and a thickness of 2.3 mm.

[0203] Aluminum Alloy

[0204] The surface of aluminum alloy A6061-T6 (Young's modulus 68.3 GPa) was subjected to sandblasting to obtain a test piece having a width of 10 mm, a length of 45 mm, and a thickness of 3 mm.

[0205] 〈Weight average molecular weight, heat of fusion and epoxy equivalent of thermoplastic epoxy resin and phenoxy resin〉

[0206] The weight average molecular weight, heat of fusion and epoxy equivalent of the thermoplastic epoxy resin and phenoxy resin were measured by the following procedures.

[0207] (Weight average molecular weight)

[0208] The thermoplastic epoxy resin and the phenoxy resin were dissolved in tetrahydrofuran, and the results were measured under the following conditions using Prominence 501 (manufactured by Showa Science Corporation, detector: Shodex (registered trademark) RI-501 (manufactured by Showa Denko K.K.)).

[0209] Column: LF-804 manufactured by Showa Denko K.K. × 2

[0210] Column temperature: 40°C

[0211] Sample: 0.4 mass% tetrahydrofuran solution of resin

[0212] Flow rate: 1mL / min

[0213] Eluent: Tetrahydrofuran

[0214] Calibration method: Conversion based on standard polystyrene

[0215] (Heat of Fusion)

[0216] 2 to 10 mg of a thermoplastic epoxy resin and a phenoxy resin were weighed and placed in an aluminum pan, and the temperature was raised from 23°C to 200°C at 10°C / min using a DSC (DSC8231 manufactured by Rigaku Corporation) to obtain a DSC curve. The heat of fusion was calculated from the area of ​​the endothermic peak during melting of the obtained DSC curve and the weighed value.

[0217] (Epoxy Equivalent Weight)

[0218] The measured value obtained in accordance with JIS K 7236: 2001 was converted into a value based on the resin solid content. In the case of a simple mixture without reaction, it was calculated from the respective epoxy equivalents and contents.

[0219] <Implementation Test Example 1>

[0220] (Solid adhesive P-1)

[0221] In a reaction apparatus equipped with a stirrer, a reflux cooler, a gas inlet pipe and a thermometer, 203 g (1.0 equivalent) of jER (registered trademark) 1007 (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, weight average molecular weight of about 10,000), 12.5 g (1.0 equivalent) of bisphenol S, 2.4 g of triphenylphosphine and 1000 g of methyl ethyl ketone were placed, and the mixture was heated to 100°C while stirring in a nitrogen atmosphere. Dissolution was visually confirmed, and the mixture was cooled to 40°C to obtain a resin composition having a solid content of about 20% by mass. The solvent was removed from the resin composition, and the mixture was heated at 160°C for 2 hours to obtain a film-like solid adhesive (P-1) having a solid content of 100% by mass and a thickness of 100 μm. The weight average molecular weight was about 37,000. The epoxy equivalent was above the detection limit. No melting heat peak was detected in DSC.

[0222] (Joint body)

[0223] A joint body of an aluminum alloy (first metal component) and a steel plate (second metal component) shown in Table 1 was produced. For the evaluation of the open time, a joint body for the evaluation of the open time was produced by the same procedure except that a solid bonding agent was placed on the first metal component and then left to stand for 3 days, and then the second metal component was placed.

[0224] The solid adhesive P-1 cut into a size of 10 mm × 15 mm is placed on the first metal member, and then the second metal member is quickly placed thereon. The overlap between these substrates is set to a width of 10 mm and a depth of 5 mm. The solid adhesive P-1 is placed in a manner that covers the entire overlapping area between the substrates. In other words, the first metal member and the second metal member are not in direct contact with each other, and the solid adhesive is interposed therebetween, thereby preparing an unbonded laminate.

[0225] A high-frequency induction welding machine (manufactured by Seidensha Electronics Co., Ltd., oscillator UH-2.5K, press machine JIIP30S) was used to heat the metal by high-frequency induction, and the test pieces were joined together by heating and pressurization. The pressurization pressure was set to 110N (pressure 2.2MPa), and the oscillation frequency was set to 900kHz. The oscillation time was set to 6 seconds.

[0226] <Implementation Test Example 2>

[0227] (Solid adhesive P-2)

[0228] In a reaction device equipped with a stirrer, a reflux cooler, a gas introduction tube and a thermometer, 20 g of Enote (registered trademark) YP-50S (manufactured by Nippon Steel Chemical & Materials Co., Ltd., a phenoxy resin with a weight average molecular weight of about 50,000) and 80 g of cyclohexanone were loaded, and the temperature was raised to 60°C while stirring. The dissolution was confirmed by visual observation, and the resin composition with a solid content of 20% by mass was obtained after cooling to 40°C. The solvent was removed from the resin composition to obtain a film-like solid adhesive (P-2) with a solid content of 100% by mass and a thickness of 100 μm. The weight average molecular weight was 50,000, and the epoxy equivalent was above the detection limit. No melting heat peak was detected in DSC.

[0229] (Joint body)

[0230] The same procedure as in Test Example 1 was carried out except that P-2 was used as the solid bonding agent, thereby producing a bonded body and a bonded body for open time evaluation shown in Table 1.

[0231] <Implementation Test Example 3>

[0232] (Solid adhesive P-3)

[0233] The resin composition P-2 and crystalline epoxy resin YSLV-80XY (manufactured by Nippon Steel Chemical & Materials Co., Ltd.) were mixed at a mass ratio of 98:2 to obtain a solid adhesive (P-3) having a weight average molecular weight of 36,000, an epoxy equivalent of 9,600 g / eq, and a heat of fusion of 2 J / g.

[0234] (Joint body)

[0235] The same procedure as in Test Example 1 was carried out except that P-3 was used as the solid bonding agent, thereby producing a bonded body and a bonded body for open time evaluation shown in Table 1.

[0236] <Implementation Test Example 4>

[0237] (Solid adhesive P-4)

[0238] The resin composition P-2 and crystalline epoxy resin YSLV-80XY (manufactured by Nippon Steel Chemical & Materials Co., Ltd.) were mixed at a mass ratio of 94:6 to obtain a solid adhesive (P-4) having a weight average molecular weight of 35,000, an epoxy equivalent of 2,100 g / eq, and a heat of fusion of 4 J / g.

[0239] (Joint body)

[0240] The same procedure as in Test Example 1 was carried out except that P-4 was used as the solid bonding agent, thereby producing a bonded body and a bonded body for open time evaluation shown in Table 1.

[0241] <Implementation Test Example 5>

[0242] (Solid adhesive P-5)

[0243] The resin composition P-2 and crystalline epoxy resin YSLV-80XY (manufactured by Nippon Steel Chemical & Materials Co., Ltd.) were mixed at a mass ratio of 89:11 to obtain a solid adhesive (P-5) having a weight average molecular weight of 33,000, an epoxy equivalent of 1,745 g / eq, and a heat of fusion of 11 J / g.

[0244] (Joint body)

[0245] The same procedure as in Test Example 1 was carried out except that P-5 was used as the solid bonding agent, thereby producing a bonded body and a bonded body for open time evaluation shown in Table 1.

[0246] <Implementation Test Example 6>

[0247] (Solid adhesive P-6)

[0248] In a reaction apparatus equipped with a stirrer, a reflux cooler, a gas introduction tube and a thermometer, 203 g (1.0 equivalent) of jER (registered trademark) 1007 (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, molecular weight of about 4060), 12.5 g (0.6 equivalent) of bisphenol S (molecular weight 250), 2.4 g of triphenylphosphine and 1000 g of methyl ethyl ketone were placed, and the mixture was heated to 100°C while stirring in a nitrogen atmosphere. Dissolution was visually confirmed, and the mixture was cooled to 40°C to obtain a resin composition having a solid content of about 20% by mass. The solvent was removed from the resin composition, and the mixture was heated at 160°C for 2 hours to obtain a film-like solid adhesive (P-6) having a solid content of 100% by mass and a thickness of 100 μm. The weight average molecular weight was about 30,000, and the epoxy equivalent was above the detection limit. No melting heat peak was detected in DSC.

[0249] (Joint body)

[0250] The same procedure as in Test Example 1 was carried out except that P-6 was used as the solid bonding agent, thereby producing a bonded body and a bonded body for open time evaluation shown in Table 1.

[0251] <Comparative Test Example 1>

[0252] (Solid Adhesive Q-1)

[0253] Two liquids of thermosetting liquid epoxy adhesive E-250 (manufactured by Conisy Co., Ltd., a two-liquid type of bisphenol epoxy resin and amine curing agent) were mixed and applied to a release film. After curing at 100°C for 1 hour, the mixture was cooled and peeled off from the release film to obtain a film-like solid adhesive (Q-1) with a thickness of 100 μm. No melting heat peak was detected in DSC. Since the mixture was insoluble in the solvent, the epoxy equivalent and weight average molecular weight could not be measured.

[0254] (Joint body)

[0255] The same procedure as in Test Example 1 was carried out except that Q-1 was used as the solid bonding agent, thereby producing a bonded body and a bonded body for open time evaluation shown in Table 1.

[0256] <Comparative Test Example 2>

[0257] (Solid Adhesive Q-2)

[0258] As the solid bonded body Q-2, an amorphous polycarbonate film (Upperlon (registered trademark) FE2000, manufactured by Mitsubishi Engineering-Plastics Corporation, thickness 100 μm) was used. No melting heat peak was detected in DSC.

[0259] (Joint body)

[0260] The same procedure as in Test Example 1 was carried out except that Q-2 was used as the solid bonding agent, thereby producing a bonded body and a bonded body for open time evaluation shown in Table 1.

[0261] <Comparative Test Example 3>

[0262] (Solid Adhesive Q-3)

[0263] Crystalline epoxy resin YSLV-80XY (manufactured by Nippon Steel Chemical & Materials Co., Ltd.) was used as the solid adhesive (Q-3). The epoxy equivalent was 192 g / eq. The weight average molecular weight was 340. The heat of fusion was 70 J / g.

[0264] (Joint body)

[0265] The same procedure as in Test Example 1 was carried out except that Q-3 was used as the solid bonding agent, thereby producing a bonded body and a bonded body for open time evaluation shown in Table 1.

[0266] <Comparative Test Example 4>

[0267] (Joint body)

[0268] Two liquids of thermosetting liquid epoxy adhesive E-250 (manufactured by Conisy Co., Ltd., a two-liquid type of bisphenol epoxy resin and amine curing agent) were mixed and applied to the first metal member and the second metal member as in the above-mentioned test example 1, respectively, and bonded within 1 minute, and then left to stand in an oven at 100°C for 1 hour in a state fixed by a clip to cure the adhesive component, and then cooled to room temperature, thereby producing a bonded body shown in Table 1. The above-mentioned thermosetting liquid epoxy adhesive E-250 was applied to the first metal member and the second metal member, respectively, and then bonded after standing for 3 days, and the same procedure as above was performed to produce a bonded body for open time evaluation.

[0269] <Comparative Test Example 5>

[0270] 203 g (1.0 equivalent) of jER (registered trademark) 1007 (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, weight average molecular weight of about 10,000), 12.5 g (1.0 equivalent) of bisphenol S, 2.4 g of triphenylphosphine and 1000 g of methyl ethyl ketone were placed in a flask and stirred at room temperature to obtain a liquid resin composition having a solid content of about 20% by mass. The liquid resin composition was applied by rod coating on the second metal component similar to the above-mentioned Test Example 1, dried at room temperature for 30 minutes, and then allowed to stand in an oven at 160°C for 2 hours, thereby forming a solid thermoplastic epoxy resin polymer coating with a thickness of 100 μm on the surface of the second metal component. The weight average molecular weight of the coating is about 40,000. The epoxy equivalent is above the detection limit. No melting heat peak was detected in DSC.

[0271] (Joint body)

[0272] The same procedure as in Test Example 1 was followed except that the first metal member was directly disposed on the second metal member having the coating, and the joints shown in Table 1 were produced. For evaluation of the open time, the second metal member was subjected to the same procedure as above except that the thermoplastic epoxy resin polymer coating was formed on the surface of the second metal member, left to stand for 3 days, and then laminated with the first metal member, to produce a joint for evaluation of the open time.

[0273] <Comparative Test Example 6>

[0274] In a reaction device equipped with a stirrer, a reflux cooler, a gas inlet pipe and a thermometer, 20 g of フエノトート (registered trademark) YP-50S (manufactured by Nippon Steel Chemical & Materials Co., Ltd., a phenoxy resin with a weight-average molecular weight of about 50,000) and 80 g of cyclohexanone were placed, and the temperature was raised to 60°C while stirring. Dissolution was confirmed by visual observation, and the mixture was cooled to 40°C to obtain a liquid resin composition with a solid content of 20% by mass. The liquid resin composition was applied by rod coating on the second metal component similar to the above-mentioned test example 1, and allowed to stand in an oven at 70°C for 30 minutes, thereby forming a phenoxy resin coating with a thickness of 100 μm on the surface of the second metal component. The weight-average molecular weight of the above-mentioned coating is about 50,000. The epoxy equivalent is above the detection limit. No melting heat peak was detected in DSC.

[0275] (Joint body)

[0276] The same procedure as in Test Example 1 was followed except that the first metal member was directly disposed on the second metal member having the phenoxy resin coating, thereby producing a joint body shown in Table 1. For evaluation of the open time, the second metal member was subjected to the same procedure as above except that the phenoxy resin coating was formed on the surface of the second metal member, left to stand for 3 days, and then laminated with the first metal member, thereby producing a joint body for evaluation of the open time.

[0277] <Comparative Test Example 7>

[0278] (Joint body)

[0279] The same procedure as in Test Example 1 was followed except that crystalline polyamide hot melt adhesive film NT-120 (manufactured by Nippon Matei Co., Ltd., thickness 100 μm) was used as the solid adhesive to produce bonded bodies and bonded bodies for open time evaluation shown in Table 1. The heat of fusion was 60 J / g.

[0280] [Shear Adhesion]

[0281] After the bonded bodies obtained in the implementation examples 1 to 6 and the comparative examples 1 to 7 were left to stand at the measuring temperature (23°C or 80°C) for more than 30 minutes, a tensile shear adhesive strength test was performed in an atmosphere of 23°C and 80°C in accordance with ISO19095 using a tensile testing machine (universal testing machine autograph "AG-X plus" (manufactured by Shimadzu Corporation); load cell 10 kN, tensile speed 10 mm / min) to measure the bonding strength. The measurement results are shown in Table 1.

[0282] [Joining process time]

[0283] The bonding process time was measured as follows. The time from the start point to the end point was measured, starting from the time when the bonding agent first came into contact with one or both substrates constituting the bonded body and ending when the bonded body was completed. Regarding the heating and pressing time, the heating and pressing time of each bonded body shown in Table 1 was averaged.

[0284] [Recyclability]

[0285] The bonded bodies shown in Table 1 were placed on a hot plate at 200°C and heated for 1 minute, and then judged based on whether they could be easily peeled off with a force of 1 N or less. All bonded bodies were judged to be good (OK) if they could be peeled off, and unsuitable (NG) if there were any bonded bodies that could not be peeled off.

[0286] [Restorability]

[0287] In each test piece of the aluminum alloy and the steel material whose joint surface was broken after the test at 23°C in the tensile shear strength test (a layer of joint solid remained on the surface of the first metal member or the second metal member or both), the first metal member was arranged on the second metal member, and a joint body was prepared in the same manner as in the above-mentioned implementation test example 1, thereby obtaining a repaired joint body. The shear adhesion at 23°C of the above-mentioned repaired joint body was measured in the same manner as the above-mentioned test method, and it was judged to be good (OK) if it was 80% or more of the first shear adhesion, and it was judged to be unsuitable (NG) if it was less than 80%.

[0288] [Opening hours evaluation]

[0289] The above tensile shear bonding strength test was performed at 23°C using a joint body for evaluation of open time. Compared with the test pieces prepared by the methods of the above implementation test examples and comparative test examples, if the shear bonding strength is 80% or more, it is evaluated as good (OK), and if it is less than 80%, it is evaluated as unsuitable (NG). The open time evaluation of good (OK) means that the open time is long and the convenience is excellent.

[0290]

[0291]

[0292] Example 1

[0293] 〈Main body〉

[0294] The billet of aluminum alloy A6061-T6 (Young's modulus 68.3GPa) is hot extruded to produce Figure 5 The W-hat-shaped open cross-section extruded profile shown was water quenched immediately after extrusion, artificially aged (200°C x 6 hours), and then cut into 400mm lengths to prepare the main body. Figure 5 The width a1 and a2 of the first joint shown are 23.8 mm, the height b1 of the upper surface and the height b2 of the lower surface are 23 mm, the height c of the front portion is 110 mm, the depth d1 of the upper portion and the depth d2 of the lower portion are 60 mm, the depth e1 from the upper surface to the central recessed portion and the depth e2 from the lower surface to the central recessed portion are 15 mm, and the thickness t1 is 2.5 mm. The change in Young's modulus of aluminum alloy A6061-T6 generated when the blank is processed into the main body is 3% or less.

[0295] 〈Metal reinforcement〉

[0296] A 440MPa grade high strength cold rolled steel sheet JFE-CA440 (manufactured by JFE Steel Corporation, Young's modulus 203GPa) for automobile outer panels was used, and a strip material cut into a width of 157.6mm was cut by a shearing machine to prepare a metal reinforcement part with a length of 400mm. Here, the width of the metal reinforcement part 157.6mm is the same as the width of the main body part, the width of the second joint part is the same as the width a1 and a2 of the first joint part, which is 23.8mm, and the thickness t2 is 0.8mm.

[0297] The main body and the metal reinforcement were bonded by placing the solid bonding agent described in Test Example 1 in a manner to have a thickness of 200 μm in contact with the entire surface of the first bonding portion and the second bonding portion (23.8 mm×400 mm, respectively) with the main body and the metal reinforcement uniformly fixed with a binder clip in an oven at an ambient temperature of 200° C. for 30 minutes. Thus, a test sample of a bumper reinforcement having a main body and a metal reinforcement was produced.

[0298] Example 2

[0299] 〈Main body〉

[0300] The main body of Example 1 was used.

[0301] 〈Metal reinforcement〉

[0302] A 440MPa grade high strength cold rolled steel sheet JFE-CA440 (manufactured by JFE Steel Corporation, Young's modulus 203GPa) for automobile outer panels was used, and a strip material cut into a width of 157.6mm was cut by a shearing machine to prepare a metal reinforcement part with a length of 400mm. Here, the width of the metal reinforcement part 157.6mm is the same as the width of the main body part, the width of the second joint part is the same as the width a1 and a2 of the first joint part, which is 23.8mm, and the thickness t2 is 0.5mm.

[0303] The main body and the metal reinforcement were joined in the same manner as in Example 1 to produce a test sample of a bumper reinforcement including the main body and the metal reinforcement.

[0304] Example 3

[0305] Regarding the joining of the main body and the metal reinforcement, the main body is used as the first metal component, the metal reinforcement is used as the second metal component, the solid adhesive described in Implementation Test Example 2 is used, and the steps described in Implementation Test Example 2 are adopted. Otherwise, the same steps as Example 1 are adopted to produce a test sample of a bumper reinforcement having a main body and a metal reinforcement.

[0306] Example 4

[0307] Regarding the joining of the main body and the metal reinforcement, the main body is used as the first metal component, the metal reinforcement is used as the second metal component, the solid adhesive described in Implementation Test Example 3 is used, and the steps described in Implementation Test Example 3 are adopted. Otherwise, the same steps as Example 1 are adopted to produce a test sample of a bumper reinforcement having a main body and a metal reinforcement.

[0308] Example 5

[0309] Regarding the joining of the main body and the metal reinforcement, the main body is used as the first metal component, the metal reinforcement is used as the second metal component, the solid adhesive described in Implementation Test Example 4 is used, and the steps described in Implementation Test Example 4 are adopted. Otherwise, the same steps as Example 1 are adopted to produce a test sample of a bumper reinforcement having a main body and a metal reinforcement.

[0310] Example 6

[0311] Regarding the joining of the main body and the metal reinforcement, the main body is used as the first metal component, the metal reinforcement is used as the second metal component, the solid adhesive described in Implementation Test Example 5 is used, and the steps described in Implementation Test Example 5 are adopted. Otherwise, the same steps as Example 1 are adopted to produce a test sample of a bumper reinforcement having a main body and a metal reinforcement.

[0312] Example 7

[0313] Regarding the joining of the main body and the metal reinforcement, the main body is used as the first metal component, the metal reinforcement is used as the second metal component, the solid adhesive described in Implementation Test Example 6 is used, and the steps described in Implementation Test Example 6 are adopted. Otherwise, the same steps as Example 1 are adopted to produce a test sample of a bumper reinforcement having a main body and a metal reinforcement.

[0314] Comparative Example 1

[0315] The main body of Example 1 was used as a test sample of Comparative Example 1.

[0316] Comparative Example 2

[0317] Regarding the joining of the main body and the metal reinforcement, the main body is used as the first metal component and the metal reinforcement is used as the second metal component. A friction stir welding machine is used to perform friction stir welding of the first joining part and the second joining part at 1500 rpm and a feed speed of 400 mm / min from the main body side. Thus, a test sample of a bumper reinforcement having a main body and a metal reinforcement is produced.

[0318] Comparative Example 3

[0319] The main body and the metal reinforcement were joined by bolting (4 locations) using a washers treated with corrosion protection, with the main body as the first metal member and the metal reinforcement as the second metal member. Thus, a test sample of a bumper reinforcement having a main body and a metal reinforcement was produced.

[0320] evaluate

[0321] The following evaluations were performed on each test sample. The results are summarized in Table 2.

[0322] 〈Evaluation of Lightweighting〉

[0323] As an indicator of weight reduction, the mass per unit length (g / m) of each test sample was determined. The density of the aluminum alloy (A6061 alloy) constituting the main body is 2.70 g / cm 3 The density of iron constituting the metal reinforcement is 7.87 g / cm 3 The mass per unit length was evaluated as “excellent” when it was less than 2.5 kg / m, “good” when it was 2.5 kg / m or more and less than 2.7 kg / m, and “poor” when it was 2.7 kg / m or more.

[0324] 〈Evaluation of plastic deformability: Three-point bending compression test〉

[0325] use Figure 8The test was carried out on a three-point bending compression tester of the structure shown. Specifically, after the test sample was arranged on the test machine in such a way that the main body was on the upper side and the pressure head located above was located in the center of the test sample, a load of more than 5t (ton) was applied to the test sample at a displacement speed of 1mm / minute through the pressure head in an atmosphere of 25°C. Based on the obtained data, a graph of the load-displacement curve was prepared with the x-axis being the displacement (mm) and the y-axis being the load (t). From the graph, the slope of the initial linear region (between 1t and 2t) was obtained, and the parallel lines based on the slope were shifted to the right, and the displacement (residual displacement) was obtained from the intersection of the x-axis and the parallel lines when the load-displacement curve at a load of 5t intersected with the parallel lines. Next, the residual strain (%) was calculated from the displacement based on the following formula 1. Here, the residual strain can be evaluated as "good" when it is greater than 0.20% and less than 0.50%, and as "poor" when it is greater than 0.50%:

[0326] Residual strain (%) = (6 × thickness of test sample × displacement) / (distance between supporting points) 2 …Formula 1

[0327] In Formula 1, the distance between the supporting points is 300 mm.

[0328] <Evaluation of electrical corrosion resistance (insulation properties)>

[0329] Regarding electrical corrosion resistance, the insulation resistance value between the aluminum alloy (first metal component) and the steel plate (second metal component) after joining was measured using a battery-powered insulation resistance meter (MODEL3301, manufactured by Kyoritsu Electric Meter Co., Ltd.). When the output voltage was 500 V, an insulation resistance value of 5 MΩ or more was judged to be acceptable.

[0330] Table 2

[0331]

[0332] Table 2 (continued)

[0333]

[0334] result

[0335] As can be seen from Table 2, the structures of Examples 1 to 7 are lightweight, have an excellent balance between rigidity and plastic deformability, and have excellent electrical corrosion resistance.

[0336] According to the present disclosure, a lightweight automobile structural part, particularly a bumper reinforcement, having a strong bond between a main body and a metal reinforcement, and excellent in balance between rigidity and plastic deformability and excellent in electrical corrosion resistance can be manufactured with a short bonding process time and a long open time.

[0337] Industrial Applicability

[0338] The method for manufacturing an automobile structural part disclosed in the present invention can be used for manufacturing an automobile structural part, particularly a bumper reinforcement constituting a framework of a bumper structure of an automobile.

[0339] Description of Reference Numerals

[0340] 2: The first metal component

[0341] 3: Adhesive layer

[0342] 5: Second metal component

[0343] 10: Bumper panel

[0344] 20: Energy absorber

[0345] 30: Bumper reinforcement

[0346] 32: Long hole

[0347] 34: Alignment hole

[0348] 36: Bolt

[0349] 40: Collision energy absorption box

[0350] 42: Round hole

[0351] 46: Nut

[0352] 50: Body fixing components

[0353] 100: Bumper structure

[0354] 200: Main body

[0355] 202: Bending part

[0356] 210: Lower first joint

[0357] 220: Upper first joint

[0358] 230: Lower part

[0359] 240: Upper part

[0360] 250: Front

[0361] 252: Central depression

[0362] 254: Lower face

[0363] 256: Upper surface

[0364] 260: Hollow

[0365] 270: Long hole

[0366] 272: Alignment hole

[0367] 300: Metal reinforcement

[0368] 302: Bending part

[0369] 304: Strengthen the main body

[0370] 310: Lower second joint

[0371] 320: Upper second joint

[0372] 370: Long hole

[0373] 372: Alignment hole

[0374] 350: Lightweight hole

[0375] 400: Bumper reinforcement

[0376] 500: Main body

[0377] 510: 1st joint

[0378] 520: Central

[0379] 530: Lower part

[0380] 540: Upper part

[0381] 550: Front

[0382] 560: Hollow

[0383] 600: Metal reinforcement

[0384] 602: Strengthen the main body

[0385] 610: Second joint

[0386] a1: Width of the first upper joint

[0387] a2: Width of the first lower joint

[0388] b1: height of the upper surface

[0389] b2: Height of the lower surface

[0390] c: Height of the front part

[0391] d1: Depth of the upper part

[0392] d2: Depth of the lower part

[0393] e1: Depth from the upper surface to the central depression

[0394] e2: Depth from the lower surface to the central depression

[0395] h1: Width of the second upper joint

[0396] h2: Width of the second lower joint

[0397] i1: Height of the front part

[0398] i2: Depth of the main body

[0399] i3: Height of the hole

[0400] j: Width of the first joint

[0401] k1: Width of the second joint

[0402] t1: thickness of the main body

[0403] t2: Thickness of metal reinforcement

[0404] t3: Thickness of the main body

[0405] t4: Thickness of metal reinforcement

[0406] α1: Angle between the upper part and the first joint above

[0407] α2: Angle between the lower part and the first joint below

[0408] β1: The angle between the upper surface and the upper part

[0409] β2: The angle between the lower surface and the lower part

Claims

1. A method for manufacturing an automobile structural part, comprising a pre-joining process and a joining process, In the pre-joining step, a laminated body is prepared in which a first metal member, a solid bonding agent, and a second metal member to be joined to the first metal member are sequentially arranged, the solid bonding agent contains an amorphous thermoplastic resin as a main component, and the amorphous thermoplastic resin is at least one of a thermoplastic epoxy resin and a phenoxy resin. In the bonding step, the stacked body is heated and pressurized to melt the solid bonding agent to bond the first metal member and the second metal member. The Young's modulus of the second metal member is higher than the Young's modulus of the first metal member by 5 GPa or more.

2. The method for manufacturing an automobile structural part according to claim 1, The epoxy equivalent of the amorphous thermoplastic resin is 1600 or more, or the amorphous thermoplastic resin does not contain an epoxy group, and the heat of fusion of the amorphous thermoplastic resin is 15 J / g or less.

3. The method for manufacturing an automobile structural part according to claim 1 or 2, The heating and pressurizing are performed under the conditions of 100 to 400° C. and 0.01 to 20 MPa.

4. The method for manufacturing an automobile structural part according to claim 1 or 2, The solid bonding agent before melting has any shape selected from the group consisting of a film, a rod, particles, and a powder.

5. The method for manufacturing an automobile structural part according to claim 1 or 2, The automobile structural part is a bumper reinforcement. The first metal member is a main body extending in the vehicle width direction and having at least one first joint portion. The second metal member is a metal reinforcement portion extending in the vehicle width direction and having at least one second joint portion. The first joining portion of the main body portion and the second joining portion of the metal reinforcement portion are joined by the solid bonding agent.

6. The method for manufacturing an automobile structural part according to claim 5, The metal reinforcement portion is arranged closer to the vehicle body side than the main body portion.

7. The method for manufacturing an automobile structural part according to claim 5, The main body has an open cross section, and the first joining portion of the main body and the second joining portion of the metal reinforcement are joined to form a cavity inside the main body.

8. The method for manufacturing an automobile structural part according to claim 5, The cross-section of the main body is in a hat shape.

9. The method for manufacturing an automobile structural part according to claim 5, The metal reinforcement portion has one or more holes.

10. The method for manufacturing an automobile structural part according to claim 5, The material of the main body is an aluminum alloy having a tensile strength of 350 MPa or more.

11. The method for manufacturing an automobile structural part according to claim 5, The material of the metal reinforcement part is any one metal material selected from iron, steel, Al-Si series aluminum alloy and Al-Zn series aluminum alloy.

12. The method for manufacturing an automobile structural part according to claim 5, The main body has the first joining portion at the upper and lower parts thereof, respectively. The metal reinforcement part has: a reinforcement portion main body extending in the vehicle width direction; and The second joining parts are respectively provided on the upper and lower parts of the reinforcing part body, The first joining portion and the second joining portion are joined at a joining surface intersecting with the front-rear direction of the vehicle.

Citation Information

Patent Citations

  • Bumper structure and frame structure

    JP2007284039A

  • Structural member for vehicle, and method of manufacturing the same

    JP2011020471A

  • Method for manufacturing composite reinforcement member and the composite reinforcement member

    JP2011161466A

  • Vehicular structure

    JP2018161946A